Tom Thumb VS Issun Boshi: A comparative study - Tri Arie Bowo; Donal Fernado Lubis; Nurul Alifia Zettyra (Universitas Aki, 2023)
The purpose of this study is to compare two stories with the same concept, namely stories about 1-inch humans from two different cultures, namely from British culture represented by the story of Tom Thumb and from Japanese culture represented by the story of Issun Boshi. This study uses a Comparative Literature approach that focuses on Zepetnek's theory of comparisons of literary works with different languages or cultures. Qualitative descriptive is used for the method in this study with a research design that is looking for similarities, differences, and the values contained in the two stories. The results obtained from this study are similarities such as 1. the main character's body size is 1 inch, 2. the origin of the main character's birth comes from prayer, 3. the main character's profession which is a knight, 4. setting of place at the beginning and the end of the story, 5. and the enemy of the main character who is a giant. In addition, differences were found, namely 1. differences in the nature of the main character, and 2. the ending of the story. The differences in the two stories are due to differences in family values. The family value found in Issun Boshi's is responsibilities, while the family value found in Tom Thumb's is self-reliance.